2021
DOI: 10.1039/d0cs01056a
|View full text |Cite
|
Sign up to set email alerts
|

The challenges, achievements and applications of submersible superhydrophobic materials

Abstract: Addressing the unique challenges faced in designing submersible superhydrophobic materials, framing current research, and exploring future research direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 246 publications
(520 reference statements)
0
72
0
Order By: Relevance
“…Superhydrophobic (SHP) materials have drawn increasing attention as a promising mitigation strategy against protein fouling. SHP surfaces provide an air plastron (AP) layer when submerged in water, which physically reduces the contact area between protein and the substrate. However, AP gradually disappears when submerged in water, , which significantly jeopardizes its stability and long-term antifouling properties of SHP materials. , Many factors impact the AP stability and SHP performance, such as pressure equilibrium, liquid type, and surface-active solutes, including proteins. , Falde et al suggested that proteins affect SHP surfaces in two possible mechanisms: dissolved protein decreases the solution surface tension and the protein in the solution will adsorb to the solid surface, altering the solid surface energy. , Choi et al reported the strong pinning effect of protein solutions on SHP surfaces during evaporation, while the SHP remained unwetted. Accardo et al also found that the microstructured SHP surface was wetted by a lysozyme solution during droplet evaporation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superhydrophobic (SHP) materials have drawn increasing attention as a promising mitigation strategy against protein fouling. SHP surfaces provide an air plastron (AP) layer when submerged in water, which physically reduces the contact area between protein and the substrate. However, AP gradually disappears when submerged in water, , which significantly jeopardizes its stability and long-term antifouling properties of SHP materials. , Many factors impact the AP stability and SHP performance, such as pressure equilibrium, liquid type, and surface-active solutes, including proteins. , Falde et al suggested that proteins affect SHP surfaces in two possible mechanisms: dissolved protein decreases the solution surface tension and the protein in the solution will adsorb to the solid surface, altering the solid surface energy. , Choi et al reported the strong pinning effect of protein solutions on SHP surfaces during evaporation, while the SHP remained unwetted. Accardo et al also found that the microstructured SHP surface was wetted by a lysozyme solution during droplet evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…32−36 However, AP gradually disappears when submerged in water, 37,38 which significantly jeopardizes its stability and long-term antifouling properties of SHP materials. 39,40 Many factors impact the AP stability and SHP performance, such as pressure equilibrium, liquid type, 41−45 and surface-active solutes, including proteins. 5,46−48 Falde et al 5 suggested that proteins affect SHP surfaces in two possible mechanisms: dissolved protein decreases the solution surface tension 46 surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the scaffolds immersed in an aqueous solution were wetted instantaneously in the case of PCL 12 and PCL 16, and slower in the case of many-layered structures (PCL 60, PCL full). The facilitated wetting of PCL 12 and PCL 16 can be explained by easier removal of the air pockets in thinner scaffolds during immersion [51]. All scaffolds remained stable during immersion in a cell culture medium for 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, these coatings show tremendous potential in future applications as real-world superhydrophobic materials. The synthesis methodology (hot pressing) is used by a range of industries (e.g., polymer coatings in upholstery) and show the potential for implantation in many more. , The implementation of enhanced composites presents a multitude of future development options both academic and industrial research. This encompasses superhydrophobic material design but extends to formulation science, nanocomposite engineering, and the development of fabrication methodologies.…”
Section: Discussionmentioning
confidence: 99%